Six days of study. The way to reduce the efficiency of the educational process - Staroshuk, Daniela; Chernoruk, Olha; Nalyvaiko, Oleksii (Scientific notes of the pedagogical department, 2022)
This article is about the impact of a four-day, five-day, six-day school week on the productivity and academic achievement of students, as well as their morale. We considered such extremely important components of education, for example, as study time and eﬀort, which aﬀects the process of reflection, and therefore these components determine how well and deeply a student will assimilate the knowledge acquired at the university. As part of the research, a survey was also conducted, in which 165 students from various faculties of the V.N. Karazin Kharkiv National University. Respondents expressed their judgments about the six-day school week, its impact on their productivity, physical, neuropsychological and moral-emotional state. We conducted an analysis of previous works and determined that academic success does not depend on the amount of study time spent on study, but on the contrary, this process is related to motivation, good mood, neuropsychological state, degrees of fatigue and the ability to rest. We also did not ignore the aspect of anxiety, so we interviewed students about this phenomenon. 62% of respondents noted that with the beginning of the six-day study at the university, the level of anxiety increased significantly. Which certainly has a negative impact on the academic performance of students, as well as directly on the learning process.